2005
DOI: 10.1002/prot.20591
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of a 5,10‐methenyltetrahydrofolate synthetase from Mycoplasma pneumoniae (GI: 13508087)

Abstract: Mycoplasma pneumoniae 5,10-methenyltetrahydrofolate synthetase [MTHFS; also known as 5-formyltetrahydrofolate cycloligase; Enzyme Commission (EC) 6.3.3.2] belongs to a large cycloligase protein family with 97 sequence homologues from bacteria to human. To help define the molecular (biochemical and biophysical) function of the M. pneumoniae MTHFS, we have previously determined its crystal structure at 2.2 A resolution (Chen et al., Proteins 2004;56:839-843). In this current study, activity assays confirmed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Based on NMR-labelling studies, a catalytic mechanism has been proposed in which 5-formyl-THF becomes transiently phosphorylated by ATP to form a phospho-enol intermediate (Chen et al, 2005; Fig. 3c), which is entirely consistent with our observations.…”
Section: +supporting
confidence: 91%
See 2 more Smart Citations
“…Based on NMR-labelling studies, a catalytic mechanism has been proposed in which 5-formyl-THF becomes transiently phosphorylated by ATP to form a phospho-enol intermediate (Chen et al, 2005; Fig. 3c), which is entirely consistent with our observations.…”
Section: +supporting
confidence: 91%
“…It has been suggested that 5-formyl-THF cyclo-ligase forms dimers in solution and that this oligomeric state is related to the cooperative binding of its substrate 5-formyl-THF (Chen et al, 2005). While the structure presented here is, in principle, consistent with a dimeric protein, an analysis (using PISA; Krissinel & Henrick, 2005) suggests that no biologically significant interfaces are present in our structure.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Homology Model Construction-A model of the mouse MTHFS protein was constructed using the crystal structure of Mycoplasma pneumoniae MTHFS with ADP, phosphate, and 5-formylTHF bound (PDB code 1U3G; Fig. 3) (25,26). A BLAST search of the Swiss-Prot data base (27), using the SIB BLAST Network Service (28), revealed a number of sequences related to mouse MTHFS.…”
Section: Methodsmentioning
confidence: 99%
“…To date, relatively little is known about the structural basis for the mechanism of catalysis. The crystal structures of a ternary complex of MTHFS from Mycoplasma pneumoniae (mpMTHFS) with ADP and 5-formyltetrahydrofolate (20) and a binary complex of MTHFS from Bacillus anthracis (bMTHFS) with ADP (21) have been reported. Although the ATP has been depicted as hydrolyzed and modeled as ADP and inorganic phosphate in the mpMTHFS structure, the substrate 5-formyltetrahydrofolate, rather than the product 5,10-methenyltetrahydrofolate, has been modeled in the active site.…”
Section: Introductionmentioning
confidence: 99%